2023
DOI: 10.1002/aenm.202302398
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Active Species Ru‐O‐Zr/Ce Construction at the Interface of Phase‐Transformed Zirconia‐Ceria Isomerism toward Advanced Catalytic Cathodes for Li‐CO2 Batteries

Qinghua Deng,
Yong Yang,
Kai Yin
et al.

Abstract: Optimized structural support widely affects the improvement of interface structure, promoting the quantity and quality of active species simultaneously for Lithium battery cathodes. Herein, a highly dispersed and anchored active species at the interface of the Zr/CeO2(111) are achieved and are used for advanced Li‐CO2 batteries cathodes. Benefiting from the abundant Ru‐O‐Zr/Ce site, the CO2 adsorption and reduction is enhanced by the migration of the electron density in the C═O of CO2 to Ru. The established Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Ru–O–Zr/Ce showed an excellent electronic structure and improved the adsorption with CO 2 , which can lead to a superior performance of the Li–CO 2 battery. 22 This study confirmed that the regulation of precious metal-based materials could effectively promote the catalytic performance and widen their application.…”
Section: Design Of High-efficiency Catalystssupporting
confidence: 64%
“…Ru–O–Zr/Ce showed an excellent electronic structure and improved the adsorption with CO 2 , which can lead to a superior performance of the Li–CO 2 battery. 22 This study confirmed that the regulation of precious metal-based materials could effectively promote the catalytic performance and widen their application.…”
Section: Design Of High-efficiency Catalystssupporting
confidence: 64%
“…According to statistics, the global demand for 2,4-dichloro-5-fluoroacetophenone is about 7000 tons, while the domestic demand for 2,4-dichloro-5-fluoroacetophenone in China is about 4000 tons. At present, o -dichlorobenzene is widely used as a raw material in industry to produce 2,4-dichloro-5-fluoroacetophenone through nitration, fluorination, nitrochlorination, and acetylation reactions. Although these four reactions are classical, there are still some shortcomings that need improvement in the actual production. The first reaction is to react nitrate o -dichlorobenzene with mixed acid, which will generate a large amount of waste acid and cause serious environmental pollution.…”
Section: Introductionmentioning
confidence: 99%